THE INTERFACE OF SHARIA AND INTERNATIONAL HUMAN RIGHTS: The Case of Women’s Right to Education - Rofii, Ahmad (Mahkamah : Jurnal Kajian Hukum Islam, 2024)
Many Muslim countries have failed to fulfil their international obligations to endorse the standard of equality and non-discrimination in education. This has led some to assume that Islamic tradition constitutes an obstacle to the elimination of discrimination in education. This essay examines the relationship of international human rights and Islamic law, focusing on the problem of discrimination against women’s right to education. The article argues that the principle of equality and non-discrimination regarding women’s right to education constitutes a fundamental norm not only in international instruments of human rights but also in the Islamic traditions. In order to ensure the compatibility of Islamic law with international standards, a more liberal approach to understanding Islam is required. Banyak negara Muslim yang gagal dalam memenuhi kewajiban internasional mereka untuk mendukung standar kesetaraan dan nondiskriminasi dalam pendidikan. Hal ini menyebabkan sebagian orang berasumsi bahwa tradisi Islam merupakan hambatan bagi penghapusan diskriminasi dalam pendidikan. Tulisan ini mengkaji hubungan hak asasi manusia internasional dan hukum Islam, dengan fokus pada masalah diskriminasi terhadap hak perempuan untuk mendapatkan pendidikan. Artikel ini berargumen bahwa prinsip kesetaraan dan nondiskriminasi mengenai hak perempuan untuk mendapatkan pendidikan merupakan norma fundamental tidak hanya dalam instrumen internasional hak asasi manusia tetapi juga dalam tradisi Islam. Untuk memastikan kesesuaian hukum Islam dengan standar internasional, diperlukan pendekatan yang lebih liberal untuk memahami Islam.